Diagnostic criteria for Werner syndrome based on Japanese nationwide epidemiological survey. Issue 2 (23rd July 2012) - Takemoto, Minoru; Mori, Seijiro; Kuzuya, Masafumi; Yoshimoto, Shinya; Shimamoto, Akira; Igarashi, Masahiko; Tanaka, Yasuhito; Miki, Tetsuro; Yokote, Koutaro
<x xml:space="preserve">Abstract</x> Aim: Werner syndrome (WS) is an autosomal recessive disorder of progeroid symptoms and signs. It is caused by mutations in the WRN gene, which encodes a RecQ DNA helicase. The aim of this study was to revise the diagnostic criteria for Japanese Werner syndrome. Methods: A nationwide epidemiological study was carried out from 2009 to 2011, involving 6921 surveys sent to hospitals with more than 200 beds to assess existing WS diagnostic criteria, as well as additional signs of high incidence on the basis of clinical experience with WS. Results: The existing diagnostic criteria were reviewed, and signs with >90% incidence were listed as cardinal signs. Several criteria were added, including genetic testing and calcification of the Achilles tendon, whereas criteria that are practically difficult to obtain, such as measurement of urinary hyaluronic acid, were omitted. Conclusion: The 26‐year‐old diagnostic criteria for WS were revised on the basis of the results of a nationwide epidemiological study. The proposed revised criteria will facilitate simpler, faster and more robust diagnosis of WS in the Japanese population. Geriatr Gerontol Int 2013; 13: 475–481.